2023
DOI: 10.1097/prs.0000000000011055
|View full text |Cite
|
Sign up to set email alerts
|

Use of Thromboprophylaxis after Autologous Breast Reconstruction: A Cost-Effective Break-Even Analysis

Charles C. Lee,
Alexis Lo,
F. Jeffrey Lorenz
et al.

Abstract: Purpose: Post-operative venous thromboembolism (VTE) is a major source of morbidity and mortality. The use of thromboprophylaxis amongst surgeons is not well studied in autologous breast reconstruction. The purpose of this study was to determine the rate of VTE in breast cancer patients undergoing autologous breast reconstruction and to compare the cost-effectiveness of postoperative chemoprophylactic agents. Methods: The TriNetX LLC. National Health Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…The triple anti-thrombotic regimen referenced in the study consisted of preoperative low molecular weight heparin (LMWH), intraoperative heparin, and dextran. However, cessation of the regimen was associated with fewer hematomas and did not increase flap thromboembolic events [51] . Postoperative immobility is often a concern in flap patients.…”
Section: Postoperative Anticoagulationmentioning
confidence: 93%
See 1 more Smart Citation
“…The triple anti-thrombotic regimen referenced in the study consisted of preoperative low molecular weight heparin (LMWH), intraoperative heparin, and dextran. However, cessation of the regimen was associated with fewer hematomas and did not increase flap thromboembolic events [51] . Postoperative immobility is often a concern in flap patients.…”
Section: Postoperative Anticoagulationmentioning
confidence: 93%
“…The radiation-induced chronic inflammation renders vessels hypercoagulable [8] , which raises concerns for flap failure. Jakobsson et al found that hematoma was the most common reason for re-exploration after free flap, and that the use of a triple anti-thrombotic regimen was significantly associated with hematoma formation [51] . The triple anti-thrombotic regimen referenced in the study consisted of preoperative low molecular weight heparin (LMWH), intraoperative heparin, and dextran.…”
Section: Postoperative Anticoagulationmentioning
confidence: 99%